Flaked corn, wheat, and sorghum grain for growing pigs - G L Allee; Robert H Hines (Kansas Agricultural Experiment Station Research Reports, 1972)
One hundred fifty-three barrows and gilts were used to evaluate flaking of corn, wheat, and sorghum grain for weaned pigs. Flaking increased rate of gain and improved feed efficiency (9 to 10%). Pigs fed corn rations gained significantly faster and were more efficient than pigs fed sorghum grain or\ wheat; and pigs fed sorghum grain gained faster and were more efficient than pigs fed wheat, regardless of processing method.; Swine Day, Manhattan, KS, November 2, 1972
Keywords: Swine day; 1972; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 193; Swine; Flaked corn; Wheat; Sorghum grain; Growing pigs